Decay rates of Escherichia coli, Enterococcus spp., F-specific bacteriophage MS2, somatic coliphage and human adenovirus in facultative pond sludge. (1st May 2019) - Schwarz, K.R.; Sidhu, J.P.S.; Toze, S.; Li, Y.; Lee, E.; Gruchlik, Y.; Pritchard, D.L.
Abstract: The purpose of this study was to evaluate the efficacy of a waste stabilization pond (WSP) system to reduce pathogen contaminants in sludge. This included examining the factors that influence the fate and concentration of human pathogens and their indicators in two sludge layers. The decay rates of five study microorganisms were determined under in-situ conditions at a WSP. The background levels of fecal origin microorganisms were consistently detected (ranging: Escherichia coli 10 4 to 10 6, enterococci 10 1 to 10 3, F-specific bacteriophage (MS2) 10 1 to 10 3 and somatic coliphage 10 1 to 10 4  colony-forming units (CFU) mL −1, as well as 10 1 to 10 2 human adenovirus gene copies mL −1 ) in the primary facultative pond. Among microorganisms tested, the bacteria generally decayed faster than adenovirus and bacteriophage, particularly in the upper sludge layer. Due to the observed regrowth of E. coli, it may have a limited value as an indicator for pathogen removal in the wastewater stabilization ponds. The abundance of E. coli numbers within the pond biome followed changes in pond temperature over time. The results of the study suggest that viruses could survive for a long time, particularly in deeper layers (>1 metre) in the sludge, during winter months ( T 90  = 156 d). The presence of human pathogens in WSP sludge, in particular viruses, may be a barrier to its beneficial reuse in agriculture. The results indicate that additional treatment of sludge may be required to mitigate potential public health risks from reuse of sludge for agricultural purposes. Graphical abstract: Image 1 Highlights: Study of influence from physicochemical and environmental indices on pathogen loading and die-off. FIB, certain viral species and phage were measured in sludge fractions of waste stabilization pond. Decay of microbes fastest for bacteria > coliphages > virus with no decay of human adenovirus. Temperature, nutrients, season, conductivity, pH and depth influence microbial abundance. Proper WSP sludge treatment is essential for potential end-product reuse as a valuable resource.